The patchwork planning of a welfare landscape: reappraising the role of leisure planning in the Swedish welfare state. (3rd September 2021) - Pries, Johan; Qviström, Mattias
ABSTRACT: The public memory of the social democratic welfare state in Sweden often emphasizes housing, but in fact post-war planning was far more diverse. One asset which postwar planning developed over time was a landscape that materialized a range of different concerns over welfare. Even today, the impressive investments in recreational facilities and green spaces made during the high point of welfarist planning in Sweden still provides the backbone of Sweden's recreational infrastructure and areas for outdoor leisure and play. This paper highlights 'leisure planning' as a forgotten aspect of the postwar decades, and argues that the relationship between urban planning and leisure planning speaks to the patchwork character of the welfare landscape and explains why it remains elusive or even invisible in the current debate. We illustrate the making of welfare landscapes by analyzing developments in Upplands Väsby municipality, focusing on the complex interplay between leisure planning and urban planning from the 1950s to the 1980s.